Implementation of Japanese Work Ethics and Culture for Prospective Workers at LPK Tomoni Marawa Abadi - Akbar M, Ramadanil; Hasibuan, Annalisa Sonaria; Nishikubo, Eriko (International Journal of Research in Vocational Studies (IJRVOCAS), 2024)
The objective of this study was to evaluate the development of understanding in relation to Japanese work ethics and culture before and after the program. A study design based on qualitative description was utilized. The sample comprised 30 individuals who were potential workers in the field of tokutei ginou or Specified Skilled Workers (SSW) batch 3. The evaluation stage entails conducting observations and surveys to assess the extent of understanding and readiness of prospective workers to relocate to Japan, considering their acquired knowledge of work ethics and culture. The survey results and attitude assessment of prospective employees after receiving the material were overwhelmingly positive. Most of the recently admitted students at LPK Tomoni have limited familiarity with work ethics or cultural norms in Japan, particularly for those intending to pursue employment in the country. Proficient communication abilities are essential for fostering collaboration within Japanese organizations. The comments received after the conclusion of work ethic and culture training in Japan were highly positive, especially about the attitudes that would be adopted after obtaining this knowledge.